Diagnosis and management of pemphigus: Recommendations of an international panel of experts - Murrell, Dedee F. (J Am Acad Dermatol, 2018)
BACKGROUND: Several European countries recently developed international diagnostic and management guidelines for pemphigus, which have been instrumental in the standardization of pemphigus management. OBJECTIVE: We now present results from a subsequent Delphi consensus to broaden the generalizability of the recommendations. METHODS: A preliminary survey, based on the European Dermatology Forum and the European Academy of Dermatology and Venereology guidelines, was sent to a panel of international experts to determine the level of consensus. The results were discussed at the International Bullous Diseases Consensus Group in March 2016 during the annual American Academy of Dermatology conference. Following the meeting, a second survey was sent to more experts to achieve greater international consensus. RESULTS: The 39 experts participated in the first round of the Delphi survey, and 54 experts from 21 countries completed the second round. The number of statements in the survey was reduced from 175 topics in Delphi I to 24 topics in Delphi II on the basis of Delphi results and meeting discussion. LIMITATIONS: Each recommendation represents the majority opinion and therefore may not reflect all possible treatment options available. CONCLUSIONS: We present here the recommendations resulting from this Delphi process. This international consensus includes intravenous CD20 inhibitors as a first-line therapy option for moderate-to-severe pemphigus.